Design and development of UAV precision localization measurement technique for low altitude paddy field monitoring application / Azhar Jaffar ...[et al.] - Jaffar, Azhar; Mohd Arshad, Nor Hashim; M. Thamrin, Norashikin; Mohamed Zan, Noorol padzilah (Universiti Teknologi MARA, 2019)
Over the years, a new modern technology has been adapted in their agriculture system to help saving cost on plantation management. The jobs of fertilizing the crops, pesticide control, crops monitoring and harvesting are all done using automatic machinery system. By this way the farmers can maximize their production and expense less on farm management for a long period of time. All these positive development are done using the help of modern technology especially with the help of using the Global Positioning System (GPS). One of the greatest achievements by using the GPS is that the GPS has the ability to map the agriculture field so that a machine can move or works autonomously inside an assign boundaries of the field. One of the favourite modern technologies that have been used in an agricultural field is using the Unmanned Aerial Vehicle (UAV) or sometimes they called it as the drone. The UAV has the ability to do lot more of things from the air. The UAV has ability to fly at low altitude to spray the fertilizer and the pesticide and the most important task is that it can monitor the crops from the air. The movement of the UAV is usually manual controlled by the user and sometime there are also an autonomous UAV. Both of the control type has the help of the GPS for their positioning. Using the light weight UAV with the GPS will become a problem. The problem is cause by the high power consumption of the GPS to operate. This will make the UAV less flying time because of the battery consumption. The other way for the UAV is to carry extra battery on-board that will significantly reduce the load for other goods. On this work, other low cost technique to compete the GPS is introduced. Two on ground beacon at a known distance using the radio frequency (RF) signal is built and tested. The beacons transmitted signals to the receiver will shows the received signal strength indictor (RSSI). The RSSI signal will be read and analysed using a C language algorithm on the receiver and the range will be calculated and estimated using trigonometry. All these functions are created, formulated and tested thoroughly in an integrated development environment (IDE) board system by using the ATmega328P on top of the Arduino Uno. The result shows that the technique successfully implemented and shows the range accurately with a margin about 5 percent between the real range and calculated range.